2017
DOI: 10.1038/s41598-017-01379-y
|View full text |Cite
|
Sign up to set email alerts
|

NKG2D+CD4+ T Cells Kill Regulatory T Cells in a NKG2D-NKG2D Ligand- Dependent Manner in Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) features a decreased pool of CD4+CD25+Foxp3+ T regulatory (Treg) cells. We had previously observed NKG2D+CD4+ T cell expansion in contrast to a decreased pool of Treg cells in SLE patients, but whether NKG2D+CD4+ T cells contribute to the decreased Treg cells remains unclear. In the present study, we found that the NKG2D+CD4+ T cells efficiently killed NKG2D ligand (NKG2DL)+ Treg cells in vitro, whereby the surviving Treg cells in SLE patients showed no detectable expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 56 publications
1
31
0
Order By: Relevance
“…Groh et al showed that those cells promoted the cytotoxic damage against synoviocytes with anomalous expression of NKG2DLs ( 14 ). Later on, NKG2D+ CD4+ T cells have been associated with several other autoimmune diseases, such as Crohn’s disease ( 108 , 113 , 114 ), Wegener granulomatosis ( 115 , 116 ), type 2 diabetes ( 117 ), multiple sclerosis ( 118 ), and systemic lupus erythematosus (SLE) ( 119 , 120 ). Moreover, NKG2D+ CD4+ T cells accumulated in patients with MIC+ tumors ( 121 ) and cervical carcinoma ( 122 124 ).…”
Section: Nkg2d Expression On T Cell Subsets: When and Where?mentioning
confidence: 99%
See 1 more Smart Citation
“…Groh et al showed that those cells promoted the cytotoxic damage against synoviocytes with anomalous expression of NKG2DLs ( 14 ). Later on, NKG2D+ CD4+ T cells have been associated with several other autoimmune diseases, such as Crohn’s disease ( 108 , 113 , 114 ), Wegener granulomatosis ( 115 , 116 ), type 2 diabetes ( 117 ), multiple sclerosis ( 118 ), and systemic lupus erythematosus (SLE) ( 119 , 120 ). Moreover, NKG2D+ CD4+ T cells accumulated in patients with MIC+ tumors ( 121 ) and cervical carcinoma ( 122 124 ).…”
Section: Nkg2d Expression On T Cell Subsets: When and Where?mentioning
confidence: 99%
“…However, increased frequencies of NKG2D+ CD4+ T cells inversely correlated with disease activity in juvenile-onset SLE, suggesting that these T cells may also have regulatory effects ( 134 ). Moreover, a recent study showed that NKG2D+ CD4+ T cells were involved in Treg killing in an NKG2D–NKG2DL-dependent manner in SLE ( 120 ).…”
Section: Nkg2d Expression On T Cell Subsets: When and Where?mentioning
confidence: 99%
“…In addition to communication with, and regulation of, NK cells, it appears that expression of NKG2D ligands also makes macrophages susceptible to regulation by direct NKG2D-mediated killing. Autologous killing of macrophages and monocytes by NK cells or NKG2D-expressing CD4 + T cells was shown after induction of NKG2D ligand expression on monocytes by lipopolysaccharide (LPS) stimulation, in vitro culture with IL-10, or on monocytes from patients with systemic lupus erythematosus ( 44 46 ). Other observations include upregulation of NKG2D ligands by human monocytes, as well as murine macrophages and microglial cells, in response to GM-CSF and other myeloid growth factors, including FLT-3 ligand and stem cell factor ( 32 , 47 ).…”
Section: Function Of Nkg2d Ligand Expression By Monocytes and Macrophmentioning
confidence: 99%
“…Moreover, these cells are thought to exert regulatory functions which may help to preserve self-tolerance, given that failure in the recognition and clearance of damaged cells can prolong the exposure of autoantigens and also the abnormal survival of activated immune cells [13][14][15]. Some studies have suggested that this constitutive expression might be reduced in lupus patients [12,18], while an enhancement in soluble MICA (sMICA) and other NKG2D ligands has been found in patients' sera [12,13]. Some studies have suggested that this constitutive expression might be reduced in lupus patients [12,18], while an enhancement in soluble MICA (sMICA) and other NKG2D ligands has been found in patients' sera [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Between NK-dependent homeostatic functions, a low expression of MICA in PBMC allows cross-talk with T helper cells and is probably involved in peripheral tolerance [13,16,17]. Some studies have suggested that this constitutive expression might be reduced in lupus patients [12,18], while an enhancement in soluble MICA (sMICA) and other NKG2D ligands has been found in patients' sera [12,13]. Interestingly, disruption of the MICA expression pathway is an immune evasion strategy evoked by intracellular pathogens and also by cancer cells, allowing their escape from cytotoxicity [10].…”
Section: Introductionmentioning
confidence: 99%